Особенности гармонического анализа многофазных несимметричных обмоток - Дёгтев, В.Г.; Абдулкарим Хусейн Гении; Бучацкая, М.П. (Електротехніка і електромеханіка, 2012)
Peculiarities of asymmetric multiphase windings are considered. A technique of the windings harmonic analysis with a symmetrical components method application is suggested. A winding factor symmetric components concept is introduced. A universal algorithm of arbitrary multiphase windings harmonic analysis is worked out, examples of its application given.